How we solved the overcrowding problem in our emergency department. - Feferman, I (1989)
Overcrowding in emergency departments presents serious problems to both patients and hospital staff. At Scarborough (Ontario) General Hospital this problem was becoming potentially dangerous until a hospital committee instituted a series of changes that dramatically improved the situation. A geriatrician was appointed to assess and care for the increasing number of elderly and chronic care patients. The beds in various services were reallocated, and more beds were given to the medical service. Surgeons agreed to perform more surgery on an outpatient basis, and the Short-Stay and Ambulatory Procedures units were expanded to handle more procedures. In addition, the implementation of a physician-managed admission system ensured the appropriate admission of patients. The entire system is monitored, and the committee meets regularly to deal with any problems.